Avian Intestinal Mucus Modulates Campylobacter jejuni Gene Expression in a Host-Specific Manner - Looft, Torey; Cai, Guohong; Choudhury, Biswa; Lai, Lisa X.; Lippolis, John D.; Reinhardt, Timothy A.; Sylte, Matthew J.; Casey, Thomas A. (Frontiers in Microbiology, 2019)
Campylobacter jejuni is a leading cause of bacterial foodborne illness in humans worldwide. However, C. jejuni naturally colonizes poultry without causing pathology where it resides deep within mucus of the cecal crypts. Mucus may modulate the pathogenicity of C. jejuni in a species-specific manner, where it is pathogenic in humans and asymptomatic in poultry. Little is known about how intestinal mucus from different host species affects C. jejuni gene expression. In this study we characterized the growth and transcriptome of C. jejuni NCTC11168 cultured in defined media supplemented with or without mucus isolated from avian (chicken or turkey) or mammalian (cow, pig, or sheep) sources. C. jejuni showed substantially improved growth over defined media, with mucus from all species, showing that intestinal mucus was an energy source for C. jejuni. Seventy-three genes were differentially expressed when C. jejuni was cultured in avian vs. mammalian mucus. Genes associated with iron acquisition and resistance to oxidative stress were significantly increased in avian mucus. Many of the differentially expressed genes were flanked by differentially expressed antisense RNA asRNA, suggesting a role in gene regulation. This study highlights the interactions between C. jejuni and host mucus and the impact on gene expression, growth and invasion of host cells, suggesting important responses to environmental cues that facilitate intestinal colonization. IMPORTANCE Campylobacter jejuni infection of humans is an important health problem world-wide and is the leading bacterial cause of foodborne illnesses in U.S. The main route for exposure for humans is consumption of poultry meat contaminated during processing. C. jejuni is frequently found in poultry, residing within the mucus of the intestinal tract without causing disease. It is not clear why C. jejuni causes disease in some animals and humans, while leaving birds without symptoms. To understand its activity in birds, we characterized C. jejuni responses to poultry mucus to identify genes turned on in the intestinal tract of birds. We identified genes important for colonization and persistence within the poultry gut, turned on when C. jejuni was exposed to poultry mucus. Our findings are an important step in understanding how C. jejuni responds and interacts in the poultry gut, and may identify ways to reduce C. jejuni in birds.